If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(2w + 4) + 9w = 0 Reorder the terms: 9(4 + 2w) + 9w = 0 (4 * 9 + 2w * 9) + 9w = 0 (36 + 18w) + 9w = 0 Combine like terms: 18w + 9w = 27w 36 + 27w = 0 Solving 36 + 27w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 27w = 0 + -36 Combine like terms: 36 + -36 = 0 0 + 27w = 0 + -36 27w = 0 + -36 Combine like terms: 0 + -36 = -36 27w = -36 Divide each side by '27'. w = -1.333333333 Simplifying w = -1.333333333
| 5k+1=4K-11 | | -2+2x=-(4-3x) | | 12(7m+2)=6(4m-7) | | -2(n-1)=10-n | | 20f+14=13f+35 | | 3(5x-3)=51 | | 3G-6g(g-8)=42 | | 4x+5-3=5x-3x+12 | | 4x+1-6x+3+2= | | -6a-34=-5(1+7a) | | 4(r-3)=2(r+8) | | 3x-5=9x-17 | | q=11200-100p-1960 | | 3a+2=a+7 | | -2Ax^2+2Ax+2A-2Bx+b-2C=x^2 | | 27-w=14 | | x=15*90 | | 2s+2=134 | | 6x+9x-22=66-7 | | 5(3x-9)-8=5(x-3)+32 | | (2x-5)(2x-4)=0 | | q=9240-100p | | F(1)=2x-4 | | 10p^2-13p+5=0 | | -4.7v-44.2=-8.3v | | v=523.6*.75 | | 2x-18=-x+24 | | 5x+4x=-9 | | 12-9y-45=-1+y | | -3(8-8x)=-3(x+8) | | v=523.6*(3/4) | | 3(8-2x)=-3+3x |